Development of building blocks using vegetable oil and recycled aggregate - Attia Mohamed I.; Zoorob Salah; Hassan Khaled; El-husseini Hozaifa; Reid James M.; Al kuwari Mohamed S. (MATEC Web of Conferences, 2017)
The primary objective of this research was to contribute towards greater sustainability of the construction industry in the Qatar by proposing methods to reduce its dependency on primary imported materials. In this investigation, recycled and secondary aggregates (RSA) were combined with non-traditional binders to develop a unique method of manufacturing construction and building blocks. Following an extensive phase of laboratory trials and experimentation, it was realised that many types of graded mineral aggregates, when mixed with vegetable oils (virgin or waste) at optimal proportions, then compacted and thermally cured at elevated temperatures can readily generate hardened composites that have the mechanical characteristics of conventional building blocks. The resultant blocks have been named “Vegeblocks” and are viewed as viable alternatives to conventional concrete blocks. Furthermore, the research has demonstrated the feasibility of producing Vegeblocks composed of 100% recycled aggregate and discarded waste cooking oil. Based on physical and mineralogical properties, each type of aggregate has an optimum oil content for maximum compressive strength, beyond which, any additional oil will result in reduction in mechanical properties. Acceptable compressive strength values were achieved by thermally curing Vegeblocks at of 170 °C for 24 hours.